Phylogenetic relationships of the Balkan Moitessieriidae (Caenogastropoda: Truncatelloidea) - Hofman, Sebastian; Rysiewska, Aleksandra; Osikowski, Artur; Grego, Jozef; Sket, Boris; Prevorčnik, Simona; Zagmajster, Maja; Falniowski, Andrzej (Zootaxa, 2018)
The family Moitessieriidae includes minute dioecious gastropods exclusively inhabiting subterranean waters, including thermal ones. Only empty shells were collected in most species, the vast majority of them are described from their gross shell morphology alone. Several visits to a site are usually required to obtain at least some living individuals. High variability in shell morphology and the lack of diagnostic features, coupled with anticipated high levels of endemism, has resulted in a long list of nominal moitessierid species. Type specimens stored as empty shells omit unambiguous identification and delimitation of species boundaries. Due to inaccessibility of cave animals and consequent lack of material suitable for molecular analysis, the phylogenetic relationships, as well as the taxonomy of the family at genus/species level, are far from being understood. The anatomy of the family is also poorly known and provided only for a few taxa. The distinctness of the Moitessieriidae has sometimes been questioned, and their monophyly not proved. Twelve species of the Balkan Moitessieriidae are considered: two species of Paladilhiopsis, two species of Bythiospeum, six species of Iglica, Costellina turrita and Lanzaia bosnica. The shell morphology of each species, as well as the reproductive system of Paladilhiopsis and Iglica, were analysed. DNA sequences of nuclear histone H3, ribosomal 18S, ribosomal 28S and mitochondrial cytochrome oxidase subunit I (COI) were applied to infer phylogenetic relationships among the taxa. The sequences of Bythiospeum from GenBank have been used to infer relationships between Bythiospeum and Paladilhiopsis that were recently synonymized. Paladilhiopsis and Iglica are distinct, but closely related genera, as is the genus Bythiospeum, which does not occur in the Balkans. Its relationships with both former taxa remain unresolved. The Moitessieriidae are clearly distinct from all other families of the Truncatelloidea, however, their monophyly remains doubtful.